Managing Risks in Academic Entrepreneurship: The Case of SiFAR - Mohar Yusof; Leilanie Mohd Nor (Faculty of Business, President University, 2018)
The main purpose of this case study is to examine the implementation and commercialization process of Simplified Financial and Recordkeeping (SiFAR) solution, a cloud-based cash flow management solution for micro and small businesses. Background of the company and entrepreneurial academics who initiated the idea and business, and the starting up process is described. The technology adoption life cycle model and the concept of crossing the chasms are used to describe the adoption rate of the solution. A pilot project was used to test the prototype and validate several features of the solution. The social scientists and entrepreneurs found a critical success factor for technology commercialization, which is managing risk. The most important factor in managing risk is to confirm demand for the solution and the willingness to pay. Hence, funds and capital need to be focused on managing risks in order for the entrepreneurial endeavor to be successful.